Investment in Graduate Teacher Education Programme in Oyo State: Implication for Educational Planner - Oduwaiye , hoda .O.; Oluwayemisi , amaye, Esther; Olufunmilayo , Tunde, Modupe (International Journal of Educational Management, 2025)
Education is considered to be an intangible good that provides both financial and pecuniary benefits as well as contribute to the growth and development of a nation. Therefore, this study compared government and private investment in university graduate teacher education programmes in Oyo State. The objectives were to examine (i) the public cost of university graduate teacher education programmes (ii) the private cost of teacher education programmes and to compare public and private cost of university teacher education programmes in Oyo State, Nigeria. The study adopted descriptive survey. The population of the study comprised 8,456 undergraduates from federal university in Oyo. The target population was 2,418 from which 180 were sampled according to aro Taman sample size. Two instruments: Public Cost of University Teacher Education Programmes Checklist (PCUTEP); Private Cost of university Teacher Education Programmes Questionnaire (PCUTEPQJ were used. The reliability of the PCUTEQ and (PCUTEPQJ were established using Cronbach Alpha statistics with coefficient of 0. 75 and 0.80 respectively. Three research questions were raised and answered using descriptive statistics. The findings of the study were: Public cost of university teacher education for 2017 was N 528,381.59; Private cost of teacher education was N 368,353.00; The difference between public cost and private cost was N160,028.59. The study concluded that public cost of university teacher education programmes in Oyo state, Nigeria is consistently stable. It was recommended tha. public cost of university teacher education programmes should increase steadily.